The Economic and Noneconomic Benefits of Tertiary Education in Low-income Contexts - Schendel, Rebecca; McCowan, Tristan; Oketch, Moses (International Higher Education, 2014)
After many years of relative neglect, development agencies and national governments across the developing world are now considering renewing their financial commitment to tertiary education. As a result, questions about the ways that tertiary education can impact society have returned to the discourse. This article summarizes the findings of a recent rigorous review on the topic commissioned by the UK Department for International Development (DFID). The review highlights a number of important social functions of the university, many of which have not been sufficiently emphasized in debates around public funding for tertiary education.